Ante-mortem cognitive trajectories associated with Aβ and tau biomarker profiles in older adults with cerebrovascular disease: a longitudinal cohort study - Emily Rosenich; Yen Ying Lim; on behalf of the National Alzheimer’s Coordinating Center (Alzheimer’s Research & Therapy)
Abstract Background Beta-amyloid (Aβ) plaques and tau tangles are pathological hallmarks of Alzheimer’s disease (AD); however, autopsy studies reveal that most older adults also present with cerebrovascular disease (CVD) markers. It remains unclear how Aβ and tau relate to cognition in the context of concurrent CVD. In initially cognitively unimpaired older adults with CVD, this study aimed to determine ante-mortem cognitive trajectories associated with elevated Aβ and/or tau at autopsy. Methods Participants aged 65–95 classified as cognitively unimpaired at baseline from the National Alzheimer’s Coordinating Center database, with ≥ 1 follow-up between 2005 and 2015, and available autopsy/APOE data were included in this cohort study (N = 863). All participants had at least one of six CVD markers at autopsy. Participants were classified into four groups (A − T−, A + T−, A − T+, A + T+) based on semiquantitative Consortium to Establish a Registry for Alzheimer’s Disease neuritic plaque staging and Braak staging. Linear mixed models assessed rate of change in Preclinical Alzheimer’s Cognitive Composite scores, episodic memory, and executive function. Results A + T + adults demonstrated significantly faster cognitive decline on all outcomes in the ~ 10 years preceding death compared to A − T− adults (d = 0.34–0.46). Similarly, when compared to A + T − adults, A + T + adults showed significantly faster decline on all outcomes (d = 0.19–0.37). At the last visit prior to death, a greater proportion of A + T + adults (36%) received a dementia diagnosis compared to A − T+ (15%; OR = 6.00), A + T− (14%; OR = 8.00) and A − T− adults (12%; OR = 6.86), p <.001. When analyses were restricted to exclude dementia diagnoses, significantly faster decline on all outcomes (p’s < 0.001, d = 0.29–0.37) was similarly observed in A + T + adults compared to A − T− adults. Conclusions In older adults with concurrent CVD, A + T + at autopsy was associated with greater cognitive decline over 10 years preceding death compared to A − T− older adults. Faster cognitive decline in A + T + in the context of low final visit dementia diagnoses may suggest that post-mortem A + T + is associated with a steep trajectory of cognitive decline ante-mortem, but that dementia progression is not inevitable.